A Light‐Powered Single‐Stranded DNA Molecular Motor with Colour‐Selective Single‐Step Control - Anderson, Tommy; Wu, Wei; Sirbu, Olga; Tong, Keshao; Siti, Winna; Rui Liu, Xiao; Kou, Bo; Murayama, Keiji; Asanuma, Hiroyuki; Wang, Zhisong (Angewandte Chemie, 2024)
Top‐down control of small motion is possible through top‐down controlled molecular motors in replacement of larger actuators like MEMS or NEMS (micro‐ or nano‐electromechanical systems) in the current precision technology. Improving top‐down control of molecular motors to every single step is desirable for this purpose, and also for synchronization of motor actions for amplified effects. Here we report a designed single‐stranded DNA molecular motor powered by alternated ultraviolet and visible light for processive track‐walking, with the two light colours each locking the motor in a full directional step to allow saturated driving but no overstepping. This novel nano‐optomechanical driving mechanism pushes the top‐down control of molecular motors down to every single step, thus providing a key technical capability to advance the molecular motor‐based precision technology and also motor synchronization for amplified effects. Molecular motors access small length scale and have potential for precision technology. But the top‐down control of these motors is a challenge as they are molecular objects subject to stochastic fluctuations. Now a rationally designed single‐stranded DNA molecular motor demonstrates a novel nano‐optomechanical driving mechanism that pushes the top‐down control of molecular motors down to every single step.